Legislative Protection of the Principle of free Administration of Local Authorities Against Interventions by the Central Authority "The Case of Morocco and Tunisia" - Abdi, Moustafa (Journal of Legal Studies and Researches, 2020)
In order to protect the independence of local authorities and their enjoyment by exercising the constitutional principle of free administration, the supervised laws of local authorities in the Moroccan and Tunisian decentralized systems have given a set of powers and powers in a series of fields for play its role of elected bodies in the achievement of sustainable development in accordance with the political guidelines of the central state and public policies Sectoral ministries, This legislation aimed to frame the relationship between decentralized bodies and central interests by trying to trace the limits of the practice of the principle of free management of local authorities in exchange for control of the interventions of representatives of the central authority in the context of administrative control which replaced supervision, where the latter works to apply the law and ensure that the commitment of local communities ale towards laws, legislations and regulatory texts governing the exercise of their powers.